2003
DOI: 10.1051/0004-6361:20021807
|View full text |Cite
|
Sign up to set email alerts
|

On the nature of moving magnetic feature pairs around sunspots

Abstract: Abstract. Employing data recorded by the Michelson Doppler Imager (MDI) instrument on the Solar and HeliosphericObservatory (SOHO), we have identified 144 pairs of opposite magnetic polarity moving magnetic features (MMFs) in two active regions (NOAA ARs 8375 and 9236). The following results are obtained: (1) The majority of MMF pairs first appears at a distance of 1000 to 5000 km from the outer boundary of the sunspot, although MMF pairs appearing closer to the sunspot may be missed. (2) MMF bipoles are not r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
64
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(81 citation statements)
references
References 23 publications
16
64
1
Order By: Relevance
“…Based on high-resolution observations, analyses of MMF characteristics have demonstrated that some MMFs are manifestations of the penumbral Evershed flow in the sunspot moat, supporting earlier results about the magnetic connection between MMFs and the sunspot penumbra (see, e.g., Yurchyshyn et al 2001;Zhang et al 2003;Sainz Dalda & Martínez Pillet 2005;Cabrera Solana et al 2006;Kubo et al 2007). On the other hand, statistical analyses of sunspot groups also showed type II MMFs flowing out from naked spots, i.e., sunspots without a penumbra (Harvey & Harvey 1973).…”
Section: Introductionsupporting
confidence: 77%
“…Based on high-resolution observations, analyses of MMF characteristics have demonstrated that some MMFs are manifestations of the penumbral Evershed flow in the sunspot moat, supporting earlier results about the magnetic connection between MMFs and the sunspot penumbra (see, e.g., Yurchyshyn et al 2001;Zhang et al 2003;Sainz Dalda & Martínez Pillet 2005;Cabrera Solana et al 2006;Kubo et al 2007). On the other hand, statistical analyses of sunspot groups also showed type II MMFs flowing out from naked spots, i.e., sunspots without a penumbra (Harvey & Harvey 1973).…”
Section: Introductionsupporting
confidence: 77%
“…Small magnetic flux concentrations called moving magnetic features (MMFs) stream radially out from the sunspots. Though MMFs have a mixed-polarity nature , and their ability to carry away flux from the sunspot has been questioned (Zhang et al, 2003), at least the mono-polar MMFs do seem to be effective in that respect. The flux shed by spots will be subjected to a random walk along the network buffeted by supergranular motions (Lawrence and Schrijver, 1993).…”
Section: Main Laws and Intrinsic Characteristics Of Large-scale Magnementioning
confidence: 99%
“…The bipolar MMFs are not randomly orientated, but instead are aligned so that a line connecting between the centres of each polarity is roughly parallel to the radial of the sunspot, with some MMFs' orientation reflecting the twist in the sunspot penumbral magnetic field . In most cases, it is the bipolar MMF fragment furthest from the sunspot that has the same magnetic polarity as the sunspot Zhang et al, 2003). Such an orientation suggests that MMFs are formed either by U-loops in a field that originates in the canopy emanating from the sunspot which has formed dips that reach down to to the photosphere (Zhang et al, 2003;Bernasconi et al, 2002), or by Ω-loop sections of flux that have detached themselves from the sub-photospheric portion of the sunspot that have subsequently risen to the photosphere to form a sea-serpent (Wilson, 1973;Spruit et al, 1987).…”
Section: Moving Magnetic Featuresmentioning
confidence: 99%
See 2 more Smart Citations